Hubungan Ketersediaan Sumber Informasi Dan Dukungan Teman Sebaya Dengan Perilaku Sadari Sebagai Deteksi Dini Kanker Payudara Pada Siswi Kelas X Dan Xi Di SMA Negeri 01 Kota Bengkulu Tahun 2025 - Della Puspita Sari; Berlian Kando Sianipar; Kartika Murya Ningrum (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
According to WHO data in 2022, there were 2.3 million cases and 670,000 deaths worldwide; GLOBOCAN 2024 recorded breast cancer as the most common cancer (11.7%), with 685,000 deaths. In Indonesia, 65,858 new cases were recorded, with an incidence rate of 42.1 and a mortality rate of 17 per 100,000 population, and this rate is expected to increase until 2030. In Bengkulu, in 2025, Bengkulu City recorded 23 cases (aged 30–59 years), followed by Kepahiang with 22 cases, and North Bengkulu with 21 cases. This study aims to determine the relationship between the availability of information sources and peer support with BSE behavior for early breast cancer detection among 10th and 11th grade female students at SMAN 01 Bengkulu City in 2025. This study used quantitative methods with a cross-sectional design. The study sample size was 80 respondents, drawn from a total population of 400 individuals, based on the inclusion and exclusion criteria. Data were collected using a questionnaire and analyzed univariately and bivariately using the Chi-square test. The results showed that the majority of respondents had readily available information sources (41 respondents), supported peer support (31 respondents), and performed BSE well (26 respondents). Statistical tests showed a significant relationship between the availability of information sources and BSE behavior (p-value = 0.007) and a significant relationship between peer support and BSE behavior (p-value = 0.004). The researchers recommend that schools provide more visual informational media, such as posters or leaflets, about BSE steps in strategic areas such as the school health center (UKS) or the school bulletin board. Schools can collaborate with local community health centers (Puskesmas) to conduct